Pascal Häusermann et le motel L’Eau vive : une conception d’avant-garde ? - Alexandra Buvignier-Legros (Les Cahiers de l'École du Louvre)
Built by Pascal Häusermann between 1967 and 1971 using the shotcrete shell technique, the Motel L’Eau Vive is a unique ensemble in Lorraine, located in the town of Raon-l’Étape. For the hotel, the Swiss architect applied his new conception of housing and town planning linked with prospective architecture and sculpture architecture. He designed an ensemble of nine hotel units, as well as the reception area and caretaker’s lodgings, in a natural setting. The motel evokes the excitement of the 1960s and the blossoming of a new architectural type linked with the development of tourism. This ensemble has been preserved and renovated by a group of devotees who wanted to bring the site back to life.